Effect of regrind on the properties of extruded PE pipes - Mamedov, SV; Alekperov, VA; Özcanli, YL (MARCEL DEKKER INC, 2002)
In this paper, the mechanical and thermo-oxidative degradation properties of samples made from high-density polyethylene (HDPE) pipes containing regrind from 5% to 50% have been investigated and compared with the structure changes of these samples. The results of tensile strength tests under constant sigma, long- and short-term internal pressure tests, heat processes measurements, the values of density, Melt Flow Index (MFI), and Oxygen Induction Time (OIT) of samples produced from virgin resins were compared with international standards. It has been observed that the addition of regrind to raw resin in ratios 20-30% gives good results (This is due to the molecular structure of semicrystalline polymer). Since the regrind material fills amorphous part, the ratio of amorphous to crystalline parts of the virgin resin determines the amount of the regrind to be added.
Keywords: Engineering; Polymer Science